The role of protein S-acylation in vascular injury associated with metabolic disorders - Wang, Yayun; Zhu, Wenhui; Wang, Wenfan; Zhang, Jiayi; Hu, Dongsen; Shao, Huanmeng; zhou, Yingtong; Wang, Shan; Zhao, Linhua (Frontiers in Endocrinology, 2025)
Protein palmitoylation represents a prevalent form post-translational lipid modification across various organisms. This reversible and dynamic cellular process is significant in regulating the transcription and expression of downstream target genes, as well as in facilitating signal transduction. Consequently, it affects various cellular activities, including innate immunity, inflammation, glucose metabolism, lipid metabolism, and functions of the brain and heart. Vascular injury emerges as a critical target organ affected by complications associated with metabolic diseases, and the palmitoylation modifications are implicated in numerous pathological processes. This review offers an overview of current understanding on protein palmitoylation and palmitic acid, emphasizing the influence of the palmitoylation modification on cellular signal transduction in metabolic diseases and exploring its connection with metabolism-related conditions such as diabetic cardiopathy, diabetic nephropathy, and fatty liver diseases. Palmitoleic acid modification holds great promise for tackling challenges related to drug specificity, off-target effects, and delivery mechanisms in the exploration of targeted palmitoleic acid modification therapy in vivo. Moreover, methodological challenges in the joint analysis and mining of large databases, including gene databases, as well as the objective evaluation of studies on the bidirectional regulation of diseases, necessitate further investigation. These insights may provide novel insights for the development of clinical therapeutic strategies.